Reconstruction of Sea Surface Temperature Data based on the Sr/Ca of Porites Coral in Ambon Bay - Corry Corvianawatie; Sri Yudawati Cahyarini; Mutiara Rachmat Putri (Institute for Research and Community Services (LPPM) ITB, 2016)
Sea Surface Temperature (SST) data can be used to understand oceanography dynamics in Ambon Bay. However, a lack of continual and long time series in-situ SST data limited this study. To overcome this problem, the Sr/Ca composition in Porites coral taken from Outer Ambon Bay was used to reconstruct SST. The coral sample was sub-sampled monthly and analyzed using ICP-OES. Subsequently, the anchor point method was used to develop the chronology of the coral Sr/Ca based on ERSST v3b data. The regression equation results were Sr/Ca = -0.059 x SST + 10.32 (r = -0.699, n = 95, p < 0.05). The reconstructed SST based on these results was verified by in-situ data from May to November 2008. The difference was found to be 1.2-2.5 °C (Ïƒ = 0.05%). This results lead us to conclude that coral Sr/Ca reflects SST variation in Ambon Bay well. Based on the reconstructed SST, we found that the SST in Ambon Bay experiences an extreme seasonal variation, which is highly correlated to air temperature, wind speed, and length of sun radiation. Ambon Bay also experiences SST anomalies in some periods, which are dominantly affected by local atmospheric conditions rather than ENSO phenomena.